2019
DOI: 10.3164/jcbn.19-61
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary salt restriction on home blood pressure in diabetic patients with excessive salt intake: a pilot study

Abstract: The aim of the present study was to examine whether dietary salt restriction guidance is beneficial for dietary salt restriction and lowering of home blood pressure in patients with diabetes with excessive salt intake. We performed an intervention trial of 37 people with type 2 diabetes and excessive salt intake. National registered dietitians provided dietary salt restriction guidance to each patient at the start of the study. All participants were instructed to perform triplicate morning and evening home blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
(24 reference statements)
1
6
0
Order By: Relevance
“…The difference between the two groups was shown by the 95% confidence interval and the p -value. Previous studies reported that salt intake decreased from 10.3 ± 1.6 g to 9.3 ± 1.9 g/day after salt reduction guidance for type 2 diabetes [ 10 ]. From this result, the sample size was calculated based on the assumption that the daily salt intake would be reduced by 1 g in the IG and the intake would not change in the CG.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference between the two groups was shown by the 95% confidence interval and the p -value. Previous studies reported that salt intake decreased from 10.3 ± 1.6 g to 9.3 ± 1.9 g/day after salt reduction guidance for type 2 diabetes [ 10 ]. From this result, the sample size was calculated based on the assumption that the daily salt intake would be reduced by 1 g in the IG and the intake would not change in the CG.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous single-arm trial, we reported that a national registered dietitian’s guidance on salt reduction is beneficial for blood pressure management at home and for lowering the salt intake in patients with type 2 diabetes who consume it in excess [ 10 ]. In that study, daily salt intake was significantly reduced to 0.8 g/day and 0.7 g/day at 2 months and 6 months after guidance, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…(12,(20)(21)(22)(23)(24) Second, the subjects were all outpatients in a university hospital, and thus might not represent the presentation of typical Japanese type 2 diabetes. Third, we validated only total energy intake and macronutrients (protein, fat, and carbohydrate), but not the other nutrients which are beneficial (26) or unfavorable (27) for type 2 diabetes.…”
Section: Bias Precisionmentioning
confidence: 99%
“…In Japan, the number of patients with metabolic syndrome and diabetes mellitus has increased with the westernization of dietary habits. Although excessive salt intake has gained consensus as a risk factor for hypertension, the association between excessive salt intake and obesity, dyslipidemia, and diabetes has remained controversial.‍ ( 6 9 ) Although the Japanese diet is well recognized to be one of the world’s healthiest, overconsumption of soy sauce, miso, pickles and salted fish can be responsible for excessive salt intake.‍ ( 10 ) To avoid excessive salt intake, it is necessary to clarify the dietary habits that are associated with it.…”
Section: Introductionmentioning
confidence: 99%